Coal Plants, Air Pollution and Anaemia: Evidence from India. Issue 4 (3rd April 2023) - Datt, Gaurav; Maitra, Pushkar; Menon, Nidhiya; Ray, Ranjan
Abstract: We examine the impact of pollution from coal–fired power units on the anaemic status of children and women in India. The number of coal units in the district at the time of birth significantly increases the incidence of anaemia in young children as does in utero exposure. The number of coal units in the district also adversely affects the anaemic status of women, although the magnitude of impact is smaller than that for young children. The impacts are driven by the increase in PM2.5 pollution generated by coal-fired units. Our evidence points to anaemia as a significant health cost of coal-fired power generation in rapidly growing economies that use coal as a major source of fuel to meet increasing energy demands.